Graduate's perception towards entrepreneurial career choice: Role of University and Family - Umar Abdullahi Ahmed; Most Asikha Aktar; Abu Sufian Abu Bakar (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2021)
In today's dynamic world, entrepreneurship is gaining greater attention both by the policymakers and scholars because of growing unemployment problems across the globe. Entrepreneurs remain vital as they contribute to crack-down on the rising societal challenges through the generation of new employment opportunities. Despite the growing acceptance of entrepreneurship in today's dynamic & competitive environment, some graduates are not comfortable pursuing their career as entrepreneurs. What perceptions they carry regarding entrepreneurship as their career choice and who can nurture their positive entrepreneurial perceptions are crucial matters, thus encouraging researchers to conduct in-depth study along this line. By considering this issue, the present study sought to know the perceptions of university graduates regarding entrepreneurship career and who influences their perceptions. Based on the above reasons, this study was conducted in two universities in Malaysia: Universiti Utara Malaysia (UUM) and Universiti Malaysia Kelantan (UMK) and taken entrepreneurial perceptions as a function of the role of university and family. The study results reveal that 57 percent of the students want to start their career as entrepreneurs after graduation. Still, several factors can make barriers for them to enter into the business environment. In this context, the majority of students mentioned insufficiency of funds as the most significant obstacle, while the desire to get rich forces them to take such a hindrance as a challenge and the key to success in an entrepreneurial career. Though the study also identifies that both university and the family play positive roles in influencing student's entrepreneurial perceptions, the family contributes more than the university. Hence, this study hopes to contribute to the entrepreneurship literature by enhancing the understanding of the entrepreneurial perception of university graduates and also provides some basis for future research in this area. As the majority of students' perception is directly inclined towards selecting entrepreneurship opportunities as a career, the findings from the current study would also assist governmental institutions, affected agencies, academic institutions, entrepreneurial mentors, dedicated consultants, as well as counselors to enhance students' perceived feasibility of self-employment by providing them relevant start-up opportunities.